Analisis Pengendalian Bahan Baku Biji Kopi pada CV. Dewi Star Indo di Kabupaten Tabanan - PARAMITHA, GUSTI AYU DHIANA PRADNYA; DEWI, IDA AYU LISTIA; WIBAWA, MADE SATRIA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2024)
Analysis of raw material inventory control coffee beans CV. Dewi Star Indo in the district Tabanan. Management of inventory or raw material supplies must be done carefully. The cost of storing raw materials as a result of purchasing in large quantities will be very high, on the other hand, if you avoid high storage costs, the company must buy more often with a smaller capacity, this also has an impact on increasing ordering costs. Seeing this, the company must be able to determine the optimal number of orders. This study aims to determine the control of raw materials by the company, control of raw materials by the EOQ method and the total cost of the company's inventory. The data analysis method used is the EOQ method. The results showed that the company used the FIFO inventory method and ordered as much as 1000 Kg-1,500 Kg of coffee beans with a frequency of 12 times in one year the economic purchase results using the EOQ method were 4,242 Kg with a frequency of 4 times in one year. The company's safety inventory is 660 Kg and the reorder point or reorder point is 793 Kg. The total cost incurred by the company using the EOQ method to carry out the company's inventory is IDR 2,897,238.